Lichen sclerosus associated with localized scleroderma: dermoscopy contribution - Monisa Martins Nóbrega; Fernanda Cabral; Mariana César Corrêa; Carlos Baptista Barcaui; Aline Lopes Bressan; Alexandre Carlos Gripp (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Lichen sclerosus is an uncommon inflammatory dermatosis with preferential involvement of the urogenital region. The extragenital involvement is uncommon and is characterized by small rounded macules or papules, pearly white in color. The coexistence of lichen sclerosus and scleroderma plaques in most cases with extragenital location has been reported in the literature. We report a case of lichen sclerosus associated with scleroderma in children, highlighting the importance of dermoscopy in diagnosis.